Pengembangan Proyek Pemrograman Medıa Pembelajaran Interaktıf Untuk Tugas Pemecahan Masalah Pelatihan Berpıkır Komputasıonal Mahasiswa Dengan Scratch - Erwinsyah Satria; Udin Syaefudin Sa’ud; Cepi Riyana; Wahyu Sopandi; Nur Rahmiani (Jurnal Elementaria Edukasia, 2024)
Media is needed in learning to attract and make it easier for students to understand the material being taught. Interactive learning media for computational thinking material through Scratch programming as an example of a block-based programming project assignment by applying computational thinking concepts for PGSD student training has not been researched in Indonesia. The research carried out aims to develop an example of a final programming project for interactive media learning computational thinking for PGSD student programming training as a valid and practical problem solving task using the Scratch program as well as the level of competency of the programming project being created. The research carried out is of the research and development type using the ADDIE model. The research participants were 40 students from a private university in West Sumatra. Data was collected using observation, interview, artifact analysis, and questionnaire techniques. The research instrument was a questionnaire with a Likert scale filled in by material, media and research subject experts. Analysis of research data was carried out in a qualitative descriptive manner. From the development research carried out, it was found that the final project example of interactive media programming for computational thinking learning which was developed for PGSD students' computational thinking training as a problem solving task received a very good score with a score of 85.5% from the validation of material experts, media and students, 85. 2% for product practicality, and makes it easier for students to created the program because the difficulty is at intermediate level.